Perbaikan Sistem Perawatan Mesin Forming dengan Metode FMECA dan RCM Berdasarkan Analisis OEE Pada PT XYZ - Andrian Akbar Waluyo; Dzakiyah Widyaningrum (Fakultas Teknik, 2023)
PT XYZ is a manufacturing company operating in the automotive sector. One of this company's flagship products is train brake pads. In production activities there are several machines, including forming machines. Based on secondary data, it is known that this forming machine has the largest contribution to product defects. This research was conducted using the OEE, FMECA, and RCM methodology. The OEE methodology is used to identify the level of effectiveness of forming machines, the FMECA methodology is used to identify critical machines, and the RCM methodology is used to determine machine repair and maintenance intervals and determine the selection of tasks in maintenance activities. The research results show that the OEE value of the forming machine is 83.79%, which is below standard. Based on the FMECA analysis, it is known that there are 2 components that are classified as critical components, namely sheet loading and molding. So, an analysis of maintenance scheduling was carried out on these two components, it was found that the sheet loading component required maintenance every 352,016 minutes and component replacement every 11.58 days with task selection in the form of a directed time. On molding components, maintenance is carried out every 328.60 minutes and component replacement every 11.46 days with the task selection being failure discovery.